Stakeholder Networks and Collaborative Upgrading of Informal Settlements in Tomang Banjir Kanal, Jakarta - Yeremias Ndoen; Rinekso Soekmadi; Heri Purnomo; Alinda Fitriany Malik Zain (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Informal settlement upgrading requires collaborative arrangements that are responsive to local conditions and stakeholder configurations. Objective: This study maps the roles and relational dynamics of key actors involved in upgrading the Tomang Banjir Kanal informal settlement in Jakarta, Indonesia. Methods: Stakeholders were identified through in-depth interviews, field observations, and local census data. Stakeholder positions were analyzed based on their levels of interest and influence in the upgrading process, while inter-actor relationships were examined using social network analysis. Results: The findings indicate that key stakeholders in multi-actor collaboration include the West Jakarta Municipal Government/Mayor’s Office as the central operational coordination hub; the Jakarta Provincial Legislative Council (DPRD) as the actor responsible for strengthening political legitimacy, budgetary support, and oversight of sectoral agencies; and the Jakarta Provincial Housing and Settlement Agency as the technical and programmatic lead. These actors are supported by neighborhood leaders (RT/RW) and community figures who function as brokers of local aspirations and maintain social stability, as well as by the Kampung Collaboration Committee, which serves as an institutional bridge connecting government agencies, community groups, and developers. Conclusion: From a technical governance perspective, the National Land Agency (BPN) has limited direct involvement but plays an essential enabling role in resolving land tenure issues, which determine the feasibility of collaborative slum upgrading. These findings highlight the need for stronger inter-agency coordination, effective land tenure resolution, and community-based collaboration mechanisms to support sustainable and inclusive upgrading programs.